Space based thermal and airborne hyperspectral data in REE exploration − A study in Siwana ring complex, Rajasthan, India - Guha, Arindam; Pathak, Suparn; Srivastav, Sushil K.; Purohit, Ritesh; Kar, M.; Chauhan, Prakash (Advances in space research, 2025)
In this study, we aimed to identify per-alkaline granite from the associated components of granitic system (Rhyolite and felsite) in the Siwana Ring complex (SRC), Rajasthan, using thermal infrared (TIR) bands of Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) sensor. Per-alkaline granites, are regarded as one of the sources of rare earth elements (REEs). We processed ASTER thermal infrared spectral bands using emissivity normalisation algorithm for deriving spectral emissivity to detect alkali mineral rich per-alkaline granite in the SRC. In this regard, an index image composite using an alkali index (band 10/band 11) and two silica indices (band 11/band12 and band 13/band 12) is derived from ASTER TIR emissivity bands. In addition to above, an image composite using emissivity band 11, alkali index band and temperature band was used to detect per-alkaline granite from other granitoids. The above-mentioned image products were proved suitable for distinguishing per-alkaline granites. We observed strong correspondence between per-alkaline granite and REE enrichment as locations of REE anomalies are associated with per-alkaline granite. In addition to above host rock, intense chemical weathering of REE-rich granitoid and associated acid volcanics is also attributed as one of the genetic controls for the regolith-hosted REE deposits. Therefore, kaolinite-rich zones within acid volcanics i.e. rhyolitic tuff are identified using a spectral feature fitting algorithm on airborne hyperspectral data of Advanced Visible Infrared Imaging Spectrometer-Next Generation (AVIRIS-NG) sensor using kaolinite mineral spectra as reference. Spectral analysis of kaolinite-rich areas using the AVIRIS-NG dataset indicates the presence of REE indicative absorption features 540 nm, 680 nm on the AVIRIS NG image spectra of the pixels of altered/kaolinized rhyolitic tuff. These spectral features are related to electronic transition in the 4f orbitals of REE minerals and diagnostic for REEs. The study reveals the importance of conjugate utilisation of ASTER thermal bands and AVIRIS-NG hyperspectral data in discriminating REE rich peralkaline granite and altered tuffaceous rhyolite. Results are validated in the field and also using reference data identifying locations of REE enrichment.